The first determination and analysis of the complete mitochondrial genome of Ancistrus temmincki (Siluriformes: Loricariidae). Issue 5 (4th May 2021) - Meng, Fang; Yin, Xiaolong; Zhang, Tao; Zhao, Chunyan; Xue, Xianglong; Xia, Xianglong; Zhu, Xintao; Duan, Zaixian; Liu, Bingjian; Liu, Yifan
Abstract: In order to fully comprehend the evolution and kinship of fishes in the family of Loricariidae, the complete mitochondrial genome of the Loricariidae fish Ancistrus temmincki was firstly characterized in the present study. The whole mitogenome was 16, 657 bp in size and consisted of 13 protein-coding genes, 22 tRNAs, 2 rRNAs genes, a control region and origin of light-strand replication. The proportion of coding sequences with a total length of 11, 473 bp was 68.88%, which encoded 3, 813 amino acids. The genome composition was highly A + T biased (56.29%), and exhibited AT-skew (0.0661) and a negative GC-skew (–0.2740). All protein-coding genes were started with ATG except for GTG in CO1, while stopped with the standard TAN codons or a single T. The control region (D-loop) ranging from 15, 635 bp to 16, 657 bp was 1023 bp in size. Until now, there is hardly any studies on the complete mitochondrial sequence in the genus of Ancistrus, phylogenetic analysis showed that A. temmincki was most closely related to Ancistrus cryptophthalmus in the genus of Ancistrus . The complete mitochondrial genome sequence has provided a new insight into the taxonomic classification, and a more complex picture of the species diversity within the family of Loricariidae.